Ensuring vibration characteristics of reactor plant centrifugal pumping equipment - D. V. Savchuk; D. E. Bescherov; D. A. Kulikov; V. A. Panov; V. L. Patrushev; M. S. Porfiriev; S. A. Soloviev (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2023)
Requirements of low vibration and low noise level are imposed on reactor plant centrifugal pumping equipment. Computational research of vibration characteristics of centrifugal pumping is required in order to choose the optimal design alternate. Representativeness and adequacy of computational research are ensured by using verified methods of mathematical modeling. The paper presents the results of comparative analysis of various options of centrifugal pump wet end with the hydraulics master data. Hydrodynamic flow analysis was made and pump impeller loads were determined to calculate the pump rotor rotational dynamics. The computational analysis considers the rotor residual unbalance. According to the calculations carried out the pump vibration characteristics were analyzed and compared to those of the prototype pump with low vibration characteristics.